Viscoelastic properties of anionic brominated surfactants - Larry Lee,; Jumat Salimon,; Mohd Ambar Yarmo,; Misni Misran, (Universiti Kebangsaan Malaysia, 2010)
The scarcity of land based oil reserves has necessitated the exploration of off shore oil. This exploration is often carried out in pristine waters and the use of green chemicals is essential to reduce environmental degradation. In the recovery of oil and gas from rocky formations, well bore fluids such as packer fluids, fracturing fluids, conformance and permeability control fluids are extensively employed. Potassium oleate as viscoelastic surfactants gives a low partition coefficient when in contact with hydrocarbon. Bromination of the oleate chain has been shown in this work to increase the partition coefficient and still maintaining its viscoelasticity. The partition coefficient increased to ca 8% compared to negligible for potassium oleate. A gel was formed when a 20% solution of potasssium 9-bromo stearate was mixed with 8% KCl. Contacting this gel with hydrocarbon resulted in a loss of viscosity due to the improved solubility of the brominated compound in hydrocarbon. This facilitates the removal of the surfactants after its use as a fracturing fluid. The viscoelastic properties were demonstrated using a Bohlin rheometer. The graph of viscosity vs shear rate shows at first a shear rate independence up to a shear rate of 0.2 s-1 and then falling with shear rate typical of a viscoelastic fluid. The zero shear viscosity ηo varied from 18 Pa s to 220 Pa s whilst the shear viscosity at 100 s-1 ranged from 0.16 Pa s to 1.5 Pa s for surfactant concentration from 20% to 5%.